1999
DOI: 10.1016/s0550-3213(99)00462-9
|View full text |Cite
|
Sign up to set email alerts
|

Super 0-brane and GS superstring actions on AdS2 × S2

Abstract: The super 0-brane and GS superstring actions on AdS 2 × S 2 background with 2-form flux are constructed by supercoset approach. We find the super 0-brane action contains two parameters which are interpreted as the electric and magnetic charges of the super 0-brane. The obtained super 0-brane action describes the BPS saturated dyonic superparticle moving on AdS 2 × S 2 background. The WZ action contains the required coupling with 2-form flux. For GS superstring, we find the string action on AdS 2 × S 2 takes th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 28 publications
4
112
0
Order By: Relevance
“…It is demonstrated that the background field configuration associated with the superparticle satisfies the Einstein-Maxwell equations and is linked to the near horizon black hole geometries. In particular, the instance of N = 2 reproduces the κ-symmetric super 0-brane propagating in the near horizon region of the extreme ReissnerNordström black hole [25]. Concluding section 4 contains the summary and the outlook.…”
Section: Jhep04(2018)009mentioning
confidence: 91%
See 4 more Smart Citations
“…It is demonstrated that the background field configuration associated with the superparticle satisfies the Einstein-Maxwell equations and is linked to the near horizon black hole geometries. In particular, the instance of N = 2 reproduces the κ-symmetric super 0-brane propagating in the near horizon region of the extreme ReissnerNordström black hole [25]. Concluding section 4 contains the summary and the outlook.…”
Section: Jhep04(2018)009mentioning
confidence: 91%
“…For N = 2 it reproduces a super 0-brane model [25,34]. Let us discuss the issue of the κ-symmetry for N > 2.…”
Section: Reduced κ-Symmetrymentioning
confidence: 98%
See 3 more Smart Citations